Digital politics, digital histories, digital futures : new approaches for historicising, politicising and imagining the digital - Kuntsman, Adi; Xin, Liu (Digital activism and society: politics, economy and culture in network communication, 2023)
Global politics has been completely transformed by the rise of digitalisation and the politicised use of everyday digital communication tools by ordinary people in citizen engagement and mass protest. And yet, digital politics as a field is rarely explored holistically and interdisciplinary beyond a narrow focus on digital activism, digital warfare or Internet governance. Digital Politics, Digital Histories, Digital Futures addresses this gap. Bringing together contributions from junior and experienced scholars, the book examines digital politics theoretically, methodologically, and ethically, offering interdisciplinary perspectives and innovative pedagogies. The first part of the book presents research chapters that look at misinformation and reactionary online activism, digital imperialism and capitalism, future internet governance, digital memory, digital waste, and environmental imagination. The second part showcases several creative and experimental tools for studying digital politics historically, and for analysing and creating future imaginaries of digital politics. By sharing these tools and reflecting on the process of their creation, the book aims to simultaneously push the boundaries of, and inspire new teaching and research in, the field of digital politics.